Ethanol Reforming in the Dynamic Plasma - Liquid Systems - Chernyak, Valeriy Ya.; Martysh, Eugen V.; Olszewski, Sergei V.; Yukhymenko, Vitalij V.; Sidoruk, Sergei M.; Nedybaliuk, Oleg A.; Prysiazhnevych, Iryna V.; Shchedrin, Anatolij I.; Levko, Dmitry S. (IntechOpen, 2011)
None